Molecular Basis of Water Activity in Glycerol–Water Mixtures - Nakagawa, Hiroshi; Oyama, Taiji (Frontiers in Chemistry, 2019)
Water activity (Aw) is a reliable indication of the microbial growth, enzymatic activity, preservation, and quality of foods. However, a molecular basis of Aw is still under debate in multiple related disciplines. Glycerol–water mixtures can provide a variation of Aws by controlling the ratio of glycerol and water. In this study, the molecular basis of Aw was examined by using differential scanning calorimetry (DSC), attenuated total reflection Fourier-transform infrared spectroscopy (ATR-IR), and incoherent quasi-elastic neutron scattering (IQENS) based on moisture sorption isotherms of glycerol–water mixtures. Three regions were identified and classified based on DSC results. DSC showed that bulk-like water existed at Aw > ≈ 0.7 at 27 °C. Hydrogen bonding related molecular vibrations were analyzed by ATR-IR, which indicated that the OH stretching in water molecules is significantly different for Aw > ≈ 0.7. Translational diffusive and/or rotational motions in time and space analyzed by IQENS appeared when Aw > ≈ 0.7, and are correlated with hydrogen bonding related local vibrational dynamics in the glycerol–water mixtures. More importantly, Aw values of glycerol–water mixtures can be explained by the hydrogen bonding network and molecular dynamics of water in the solution. We discuss the implications of Aw in the preservation of food at the molecular level.